Isolation and phylogenetic analysis of canine distemper virus among domestic dogs in Vietnam - NGUYEN, Dung Van; SUZUKI, Junko; MINAMI, Shohei; YONEMITSU, Kenzo; NAGATA, Nao; KUWATA, Ryusei; SHIMODA, Hiroshi; VU, Chien Kim; TRUONG, Thuy Quoc; MAEDA, Ken (Journal of Veterinary Medical Science, 2017)
Canine distemper virus (CDV) is one of the most serious pathogens found in many species of carnivores, including domestic dogs. In this study, hemagglutinin (H) genes were detected in five domestic Vietnamese dogs with diarrhea, and two CDVs were successfully isolated from dogs positive for H genes. The complete genome of one isolate, CDV/dog/HCM/33/140816, was determined. Phylogenetic analysis showed that all Vietnamese CDVs belonged to the Asia-1 genotype. In addition, the H proteins of Vietnamese CDV strains were the most homologous to those of Chinese CDVs (98.4% to 99.3% identity). These results indicated that the Asia-1 genotype of CDV was the predominant genotype circulating among the domestic dog population in Vietnam and that transboundary transmission of CDV has occurred between Vietnam and China.